γδ T Cells May Aggravate Acute Graft-Versus-Host Disease Through CXCR4 Signaling After Allogeneic Hematopoietic Transplantation - Wu, Ning; Liu, Ruoyang; Liang, Shuang; Gao, Haitao; Xu, Lan-Ping; Zhang, Xiao-Hui; Liu, Jiangying; Huang, Xiao-Jun (Frontiers in Immunology, 2021)
Graft-versus-host disease (GVHD) is a pathology in which chemokines and their receptors play essential roles in directing the migration of alloreactive donor T cells into GVHD organs, thereby leading to further target tissue damage. Currently, acute GVHD (aGVHD) remains a major cause of high morbidity and mortality in patients who underwent allogeneic hematopoietic cell transplantation (alloHCT). The identification of immune cells that correlate with aGVHD is important and intriguing. To date, the involvement of innate-like γδ T cells in the pathogenesis of aGVHD is unclear. Herein, we found that primary human γδ T cells did not directly trigger allogeneic reactions. Instead, we revealed that γδ T cells facilitated the migration of CD4 T cells via the SDF-1-CXCR4 axis. These results indicate indirect regulation of γδ T cells in the development of aGVHD rather than a direct mechanism. Furthermore, we showed that the expression of CXCR4 was significantly elevated in γδ T cells and CD4 and CD8 T cells in recipients who experienced grades II-IV aGVHD after alloHCT. Consistently, CXCR4-expressing γδ T cells and CD4 T cells were induced in the target organs of mice suffering aGVHD. The depletion of γδ T cells in transplant grafts and treatment with AMD3100, an inhibitor of CXCR4 signaling, delayed the onset of aGVHD and prolonged survival in mice. Taken together, these findings suggest a role for γδ T cells in recruiting alloreactive CD4 T cells to target tissues through the expression of CXCR4. Our findings may help in understanding the mechanism of aGVHD and provide novel therapeutic targets.